Compact Multi-Channel Long-Wave Wideband Direction-Finding System and Direction-Finding Analysis for Different Modulation Signals - Hangyu Lu; Shun Wang; Xin Xu; Yicai Ji; Xiaojun Liu (Applied Sciences)
This paper presents an optimized long-wave (10–300 kHz) wideband direction-finding system for scientific research. The antenna unit of the system comprises one vertical electric field sensor and two horizontal magnetic field sensors oriented in the north–south and east–west directions, respectively. The overall design prioritizes compactness, engineering feasibility, and ease of deployment, enabling the effective reception of long-wave radio signals within the 10–300 kHz range. The magnetic field sensitivity reaches <semantics>8<mspace width="0.166667em"></mspace>fT/<msqrt>Hz</msqrt>@10<mspace width="0.166667em"></mspace>kHz</semantics>, while the electric field sensitivity achieves <semantics>3.2<mspace width="0.166667em"></mspace>μV/m/<msqrt>Hz</msqrt>@10<mspace width="0.166667em"></mspace>kHz</semantics>. The overall sensitivity of the receiver is <semantics>1<mspace width="0.166667em"></mspace>μV</semantics> (300 Hz bandwidth, 10 dB signal-to-noise ratio). The synchronization accuracy of the system is within 10 ns. Theoretically, with a baseline length of 5 km and a signal incidence angle ranging from 9.9° to 170.1°, the direction finding error is less than 2°. Additionally, direction-finding methods for MSK and ASK modulated signals are analyzed. To evaluate the system’s actual performance, initial measurements were conducted in Qingdao, Shandong.